Transparency in fisheries governance: Achievements to date and challenges ahead. (February 2022) - Guggisberg, Solène; Jaeckel, Aline; Stephens, Tim
Abstract: Globally, fisheries continue to face a range of pressures that can be addressed by more effective national, regional, and international fisheries governance. Increasing the transparency of decision-making and implementation of adopted measures is widely recognised as forming part of the solution to this challenge. While transparency has emerged as a good governance principle in general, it is embedded in specific international law obligations when it comes to fisheries. For fisheries management, it is crucial that relevant data be available to inform decisions and that the process be inclusive. Ensuring inclusive decision-making relies not only on the participation of outsiders but also on the equality of States in the negotiations leading to a decision. Furthermore, transparency serves important functions in relation to compliance and accountability: putting information on vessels, States, international organisations or even private actors in the public domain enables scrutiny, might encourage compliance, and builds trust in the regime. Several lessons for fisheries management arise from the contributions to this special issue of Marine Policy . First, the positive impact of transparency ought not to be accepted without a thorough examination of its implementation in practice. Second, transparency in a substantive sense does not mean simply the availability of data; it must also focus on information of high quality and usability for specific stakeholders. Finally, keeping in mind the ultimate purpose of sustainability, transparency is but one stone in the larger process of building legitimate and effective regimes for managing shared resources.